Pinson, Halleli, Bunar, Nihad, and Devine, Dympna (eds.). Research Handbook on Migration and Education. - Tang, Jiaqi; Bi, Huichao (Journal of Comparative Family Studies, 2025)
The article focuses on the "Research Handbook on Migration and Education," which addresses the educational challenges faced by the growing global migrant population, now exceeding 280 million, as reported by the International Organization for Migration. It highlights the unique obstacles that migrant families encounter, such as language barriers and socio-economic disparities, and emphasizes the need for education systems to evolve from monocultural to multicultural environments that promote inclusion. The handbook compiles interdisciplinary research and practical strategies across 36 chapters, exploring themes like educational mobility, community collaboration, and the intersection of migration policy and educational practices. It advocates for inclusive educational approaches that recognize the critical role of family involvement in supporting migrant children's academic success and calls for transformative actions to address systemic inequalities in education.